Learning obstacle of proportion learning based on proposional reasoning level: A case study pre-service mathematics teachers - Sugiarni, Rani; Herman, Tatang; Suryadi, Didi; Prabawanto, Sufyani; Jusniani, Nia (Universitas Hamzanwadi, 2025)
The proportion has emerged as an important mathematical topic in high school because of its foundation in other mathematics topics. This study aims to identify the learning barriers of pre-service mathematics teachers (PMT) based on the material proportion and level of reasoning proportion. This study implemented Didactical Design Research (DDR) and used qualitative research methodologies within an interpretive paradigm. The research participants were 25 PMTs from a seventh-semester candidate teacher at a private college in Cianjur, Indonesia. The data collected from the test results and interviews were analyzed using procedures such as identification, clarification, reduction, and verification. We then present the findings in a narrative format. Langrall and Swafford categorized the results of written tests at the proportional-reasoning level. Based on the results, the PMT at the varied proportional level but at the nonproportional level 0 identified learning obstacles, which include ontogenetic obstacles, epistimology obstacles, and didactic obstacles. The results of this study are expected to be used as a basis for designing hypothetical learning for school mathematical research in future PMT.